Kajian Efisiensi Saluran Sekunder Daerah Irigasi Krueng Aceh Kabupaten Aceh Besar - Harifin Harifin; Meliyana Meliyana; Tety Sriana (Jurnal Teknik Sipil Unaya, 2020)
Irrigation efficiency is defined as the ratio between the amount of water supplied less water loss and the amount of water supplied. Water losses that occur during water supply are caused mainly by seepage in the wet section of the channel, evaporation (generally relatively) small and operational losses. This study aims to determine how much the flowrate, and efficiency of the secondary channel Blang Bintang in the channel and the amount of water loss due to evaporation and seepage. Based on the analysis that has been done, obtained the amount of secondary flow flow Blang Bintang on the channel section that is to flow upstream at the channel of 1.58 m3 / sec and downstream of the channel at 1.29 m3 / sec. The maximum evaporation value found in August is 3.23 mm / day. The seepage value (S) of the Blang Bintang secondary channel on the channel section is the same for each month which is 0.01 m3 / sec / km. The value of the water debit lost in the secondary channel is 0.29 m3 / sec with a percentage of water loss of 18.63%. Is 81.37%. Means that the channel is less efficient in delivering water, the allowable efficiency in the secondary channel is 90%.